Participants with pharmacologically impaired taste function seek out more intense, higher calorie stimuli. (1st October 2017) - Noel, Corinna A.; Sugrue, Meaghan; Dando, Robin
Abstract: Objective: Research suggests a weaker sense of taste in people with obesity, with the assumption that a debilitated taste response increases the desire for more intensely tasting stimuli to compensate for decreased taste input. However, empirical testing of this supposition remains largely absent. Method: In a randomized, repeated measures design, 51 healthy subjects were treated with varying concentrations of a tea containing Gymnema sylvestre ( GS ), to temporarily and selectively diminish sweet taste perception, or a control tea. Following treatment in the four testing sessions, taste intensity ratings for various sweet stimuli were captured on the generalized Labeled Magnitude Scale (gLMS), liking for real foods assessed on the hedonic gLMS, and optimal level of sweetness quantified via an ad-libitum mixing task. Data were analyzed with mixed models assessing both treatment condition and each subject's resultant sweet response with various taste-related outcomes, controlling for covariates. Results: GS treatment diminished sweet intensity perception (p < 0.001), reduced liking for sweet foods (p < 0.001), and increased the desired sucrose content of these foods (p < 0.001). Regression modeling revealed a 1% reduction in sweet taste response was associated with a 0.40 g/L increase in optimal concentration of sucrose (p < 0.001). Discussion: Our results show that an attenuation in the perceived taste intensity of sweeteners correlates with shifted preference and altered hedonic response to select sweet foods. This suggests that those with a diminished sense of taste may desire more intense stimuli to attain a satisfactory level of reward, potentially influencing eating habits to compensate for a lower gustatory input.